Towards a Critical Political Economy of Surveillance and Digital Authoritarianism - Akbari, Azadeh; Wood, David Murakami (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
In this short piece, we suggest some directions for considering the interrelated questions of postcolonial authoritarianism, platform capitalism, and surveillance. We first put forward a three-level model of contemporary digital authoritarianism, which argues for a prism of discourses, practices, and infrastructures, before we turn specifically to the political economy of contemporary capitalism. Here, we shift the focus away from only either state and/or the individual and the conventional entities in between, to consider the new platform actors driving authoritarianism and digital surveillance in the twenty-first century.